Exploration smtAB Gene of Lead (Pb) Resistance in Isolate Bacteria from Lapindo Mud - Arifani, Diah; Holil, Kholifah; Syarifah, Umaiyatus (Proceedings of the International Conference on Green Technology, 2017)
Indigenous bacteria are bacteria that have the ability to reduce harmful compounds such as heavy metals. Indigenous bacteria isolated from Lapindo mud are known to have lead capability. This ability is due to the presence of a resistant gene possessed by the bacteria. One of these genes is the smtAB gene that works to produce heavy metal-binding proteins, namely metallothionein . Each bacterium has a different heavy metal resistance gene. Therefore this study aims to determine the species of bacteria that have genes smtAB in bacterial isolates obtained from Lapindo Mud. The type of research conducted is descriptive qualitative. In this study, there are several stages, plasmid DNA isolation by alkaline lysis method, smtAB gene amplification and sequence confirmation by amplicon sequencing results. PCR amplification results of subsequent visits similarity (similarity) sequence gene sequencing results with the data smtAB from GenBank and processed using Bioedit. Based on the results of DNA plasmid amplification Bacillus subtilis isolated from Lumpur Lapindo showed that the bacterial isolates contained genes smtAB . While data sequencing results showed that Bacillus subtilis has similarity with Synechococcus sp. IU 625 metallothionein smtAB gene complete cds value 0,5.